Religious Value Internalization through Youth Religious Activities: Strengthening Faith and Character Development in Community-Based Education - Ilham Nopri Yadi; Zulkarnain zulkarnain; Suhiman Mastofa (2 issues per year (June and December), 2025)
The rapid development of globalization and technology has created both opportunities and challenges for youth, particularly regarding moral degradation, secular lifestyles, and weakening religious adherence. Within this context, strengthening religiosity through structured community-based initiatives becomes crucial. This study aims to explore the internalization of religious values among Muslim adolescents through organized religious activities in Lubuk Kumbang Village, Karang Jaya District, South Sumatra, Indonesia, emphasizing the role of community participation in fostering faith and character development. Employing a qualitative descriptive design, data were collected through interviews with religious leaders, village officials, parents, and youth participants, supplemented by observation and documentation. The findings reveal that religious value internalization is achieved through daily practices such as congregational prayer, Qur’an recitation, and participation in Islamic learning centers; weekly activities including Friday prayer, Islamic study circles, recitation groups, and hadroh performances; monthly gatherings such as communal pengajian; and annual observances during Ramadan, zakat distribution, Eid celebrations, and Qurban rituals. These activities contribute significantly to enhancing adolescents’ religious knowledge, discipline, moral responsibility, and social behavior, while simultaneously fostering solidarity and spiritual resilience within the community. In conclusion, the study demonstrates that youth religious activities not only function as cultural traditions but also as transformative educational practices that bridge family, school, and society in cultivating spiritual awareness and ethical conduct. The implications underscore the need for sustainable community-based programs to institutionalize religious values as a preventive strategy against moral decline in the era of globalization, reinforcing that faith-driven education remains vital for shaping resilient, responsible, and spiritually grounded youth.